ANALISIS PENGEMBANGAN WEBSITE INTERAKTIF DAN USABILITY LAYANAN INFORMASI PENDAFTARAN PROGRAM BANTUAN PADA DINAS SOSIAL KOTA MEDAN - Devraz, R.W.; Sitanggang, Jelita Sari; Pardede, Eva Damayanti; Sihombing, Oloan (Jurnal Teknik Informasi dan Komputer (Tekinkom), 2025)
This study suggests the development of an interactive website to improve user-friendly services and information and make registration for social assistance programs easier at the Dinas Sosial of Medan City. The main objective of the research is to address the problems that people often face: ineffective online registration process and lack of information about social assistance programs. The research method was conducted by creating a website with an easy-to-use user interface and testing it with user research methods to ensure that it was easily accessible and useful. The results show that a clear, complete, and easy-to-use website can increase transparency and public engagement in social assistance programs. Therefore, it is hoped that the creation of this interactive website will be an effective tool to improve the availability of information and services and make it easier for the public to get the assistance they need.